2009
DOI: 10.1517/14656560903201699
|View full text |Cite
|
Sign up to set email alerts
|

Fungal chitin-glucan scaffold for managing diabetic xerosis of the feet in menopausal women

Abstract: The increased moisturization of the SC of the sole probably improves the desquamation process and reduces xerosis of the soles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…Foot amputation after bacterial infection is still a serious complication in patients with diabetes. 15 Our results indicate an increased degree of skin xerosis linked with the duration of diabetes associated with desquamation and pruritus in our diabetic patients. Emollient therapy can correct all these alterations.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Foot amputation after bacterial infection is still a serious complication in patients with diabetes. 15 Our results indicate an increased degree of skin xerosis linked with the duration of diabetes associated with desquamation and pruritus in our diabetic patients. Emollient therapy can correct all these alterations.…”
Section: Discussionsupporting
confidence: 49%
“…Skin dryness and reduced elasticity may lead to cracking in the skin followed by bacterial invasion and infection. Foot amputation after bacterial infection is still a serious complication in patients with diabetes 15 . Our results indicate an increased degree of skin xerosis linked with the duration of diabetes associated with desquamation and pruritus in our diabetic patients.…”
Section: Discussionmentioning
confidence: 53%
“…It was reported that morbidly obese patients have dry skin and impaired skin barrier repair 1 . In addition, it was also reported that xerosis of feet commonly occurs in menopausal women as well as diabetic patients due to corneocyte accumulation 14 . In our study, the incidence of xerosis in two groups was close to each other.…”
Section: Resultsmentioning
confidence: 99%
“…Wzmacniają barierę naskórkową, przywracają prawidłowy poziom lipidów w skórze, redukują złuszczanie, zmiany wypryskowe, nadkażenia bakteryjne i grzybicze, łagodzą także świąd skóry. Profilaktyka suchej skóry i świą-du jest niezwykle prosta, wymaga jednak od pacjenta systematyczności w używaniu emolientów, któ-rych regularne stosowanie wzmacnia i odbudowuje barierę naskórkową, redukuje złuszczanie, zmiany wypryskowe, nadkażenia bakteryjne i grzybicze oraz świąd skóry [41][42][43][44]. Mimo że emolienty stanowią grupę dermokosmeceutyków szeroko stosowanych w lecznictwie dermatologicznym, doniesień na temat ich skuteczności w terapii suchej skóry i zapobieganiu powikłaniom u diabetyków jest stosunkowo niewiele.…”
Section: Pielęgnacja Skóry Cukrzycowejunclassified